Assessing Community Vulnerability to the 2010 Merapi Eruption: an Analysis of Exposure, Sensitivity and Adaptive Capacity - Jafar (Sumatra Journal of Disaster, Geography and Geography Education, 2025)
Mount Merapi is one of the most active volcanoes in Indonesia. In the past century, Merapi erupted several times and caused damage and loss of life to the surrounding communities, especially in Cangkringan Sub-district, Sleman. However, it does not stop the community from inhabiting the volcano’s slopes. One of the main reasons is the communities rely on their livelihood on livestock and agriculture within those areas. This study assessed the vulnerability of the communities who live on the slopes of Merapi by identifying three key aspects: exposure, sensitivity, and adaptive capacity. This study employs a qualitative approach using secondary data from scientific literatures, hazard maps, government reports, and statistical records. Overall, the findings indicate that community vulnerability results from the intersection of persistent exposure, socioeconomic sensitivity, and uneven adaptive capacity. Strengthening disaster risk reduction in Merapi’s hazard zones requires not only enhancing institutional preparedness but also addressing livelihood dependence and local cultural dimensions. The study underscores the importance of integrating social vulnerability assessment into volcanic disaster management and resilience planning.